Morphology and function of the reproductive system of representatives of the genus Uca - Lautenschlager, Agnes D.; Brandis, Dirk; Storch, Volker (Journal of morphology, 2010)
The morphology of the reproductive organs of three species of fiddler crabs, Uca ecuadoriensis, Uca c.f. forcipata, and Uca tangeri were investigated to subsequently produce a model of their mode of operation. Vulva, vagina, and spermatheca in females, and the first and second gonopods in males were examined by applying histological techniques and electron microscopy. In all three species, vulva and vagina conform to the concave type, and the spermatheca complies with the ventral type. The tissue of the oviduct orifice is enlarged and bulges into the lumen of the spermatheca. Differences between the three species are apparent in the organization of the spermatheca, especially in the distribution and structure of glandular epithelium: In U. ecuadoriensis and U. c.f. forcipata the largest proportion of the spermathecal wall is lined with cuticle and only a small area consists of glandular epithelium, while in U. tangeri almost all of the lining is glandular. Furthermore, the glandular epithelia of the species differ in their histology and ultrastructure: In U. ecuadoriensis it is tubular and multilayered, while in U. c.f. forcipata it is mono-layered. U. tangeri finally has both forms of this tissue. In the males, the terminal segments of the first gonopod exhibit a tight fit to female organs and narrow, tightly sealed sperm channels. These features suggest a tendency towards minimizing loss of fluids, which can be interpreted as an adaptation to mating on land. The tight fit of male gonopod and female opening seem to be protection from interbreeding, which points toward a strong sexual selection. In the terrestrial environment, these originally aquatic organisms experience serious competition for resources; therefore there is pressure on successful reproduction. According to the current results a model of the process of fertilization and egg-laying involving the investigated organs was generated. J. Morphol., 2010. © 2010 Wiley-Liss, Inc.